Isolasi dan Potensi Enzim Hidrolase Bakteri Simbion Padina sp. dari Pantai Lengkuas Belitung - Nur Jannah, Siti; Hanifa, Yumna Rahmadias; Utomo, Adi Budi; Dian Prambodo, Ashar Kurnia; Lunggani, Arina Tri (Bioma : Berkala Ilmiah Biologi, 2021)
Marine organism is one of the riches in the ocean of Indonesia. The benefits of sea use for new products produced are widely used and have high market demand. Enzymes that have marine interests have unique properties and have good benefits for industry. This study aims to isolate the bacteria that have symbionts with Padina sp and determine the potential of the enzyme hydrolase produced by these bacteria. Isolation is done by the spread plate method. Pure isolates obtained were then tested for the potential of the enzyme hydrolase on selective media. Clear zone measurements are performed to determine which bacterial isolates are good for enzyme production. The results obtained by 6 isolates of pure bacteria, all of which include Gram negative bacteria that form bacilli. All isolates had the ability to produce different Protease, Lipase, Amylase and Cellulase enzymes. The enzymes obtained from these symbiotic bacteria are expected to be used for industrial-scale production in Indonesia. In addition, the presence of this symbiont bacteria is able to reduce the level of exploitation of Padina sp and contribute to preserving the marine ecosystem.